The Impact of Interactive Digital Media on Students’ Motivation and Academic Achievement - Fitria Nurulaeni; Rizki Rohmat Nur Alim Isnaini; Suraya Mukadar; Marito Ritonga; Andi Cici Thania (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study investigates the impact of interactive digital media on students’ motivation and academic achievement in secondary education using an empirical quantitative approach. A cross-sectional explanatory design was implemented with stratified random sampling to ensure representation across grade levels and academic tracks. Data were collected through structured questionnaires measuring interactive digital media exposure and learning motivation, complemented by documented academic achievement scores to reduce common-method bias. The measurement model demonstrated satisfactory construct validity and reliability based on confirmatory factor analysis and internal consistency indicators. Structural equation modeling results revealed that interactive digital media exerted a significant positive direct effect on academic achievement and an indirect effect through learning motivation. Bootstrapping procedures confirmed the mediating role of motivation, indicating that interactivity features such as feedback, learner control, and engagement affordances are critical mechanisms for academic gains. The findings suggest that the educational value of digital media is contingent on instructional integration and interactivity quality rather than mere technology availability. Implications highlight the importance of designing feedback-rich, motivation-supportive digital learning environments to strengthen student performance outcomes